Analisis Pengetahuan Kognitif Berdasarkan Dimensi Pengetahuan Materi Tekanan Zat Pada Peserta Didik Kelas VIII SMPS Katolik Mater Inviolata - Maria Magdalena Uto Koli; Rosenti Pasaribu; Egidius Dewa (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
This study aims to determine the level of cognitive knowledge based on the dimensions of knowledge of students on substance pressure material in class VIII of Mater Inviolata Catholic High School. The sampling used is Random Sampling. The sample in this study were VIII grade students of Mater Inviolata Catholic High School totaling 30 people. The data collection instrument used in this study was a cognitive knowledge test question. The results of data analysis can be concluded that the level of cognitive knowledge of students on factual knowledge is categorized as good with an average score of 84. The level of cognitive knowledge of students on conceptual knowledge is categorized as less good with an average score of 69. While the level of cognitive knowledge on procedural knowledge is categorized as less good with an average score of 74, the level of cognitive knowledge of students on metacognitive knowledge is categorized as less good with an average score of 67 and the overall level of cognitive knowledge of students based on the dimensions of knowledge is categorized as less good with an average score of 73.